Absolute and Relative Judgment Accuracy: Early Childhood Teachers' Competence to Evaluate Children's Mathematical Skills - Hosoya, Georg; Blömeke, Sigrid; Eilerts, Katja; Jenßen, Lars; Eid, Michael (Frontiers in Psychology, 2021)
This study examined German early childhood teachers’ absolute and relative judgment accuracy with respect to the mathematical skills of the children under their supervision. The two types of judgment accuracy are crucial prerequisites for pacing activities in early childhood education and offering differentiated activities adapted to children’s individual skill levels. Data from 39 early childhood teachers and 268 children were analyzed using multilevel modeling. Teachers rated children’s skills on a structured observation instrument (“Kinder Diagnose Tool”, KiDiT). Children were assessed on their mathematical skills with a standardized test (“Mathematische Basiskompetenzen im Kindesalter”, MBK-0). On average, 65% of the variation in teachers’ judgments on the KiDiT could be explained by children’s MBK-0 scores which suggests that teachers are – on average – well able to rank children within their groups. Teachers were also able to judge the mathematical level of children’s skills as assessed by the MBK-0. Neither teachers’ mathematical content knowledge (MCK), nor their mathematics pedagogical content knowledge (MPCK) or their general pedagogical knowledge (GPK) moderated the relationship between teachers’ judgments and children’s test scores or the relationship between the level of the judgments and the level of test scores. Conclusions for future research and practice are drawn.